2020
DOI: 10.1080/13676261.2020.1746757
|View full text |Cite
|
Sign up to set email alerts
|

How do social media-related attachments and assemblages encourage or reduce drinking among young people?

Abstract: Research shows that young people's online practices have become a continuous, seamless and routine part of their physical and social worlds. Studies report contradictory findings on whether social media promotes intoxication-driven drinking cultures among young people or diminishes their alcohol consumption. By applying actor-network theory, our starting point is that the effects of social media depend on what kinds of concerns mediate its use. Social media alone cannot make young people drink more or less but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 46 publications
(42 reference statements)
3
25
0
1
Order By: Relevance
“…Moreover, in our data girls are more concerned than boys about images in which they are represented in the online environment as intoxicated, a phenomenon studied more specifically elsewhere (Törrönen et al, 2020a). Also, this concern shows how female drinking behaviour faces more intensive social control and moral censure than that of young men.…”
Section: Discussionsupporting
confidence: 48%
“…Moreover, in our data girls are more concerned than boys about images in which they are represented in the online environment as intoxicated, a phenomenon studied more specifically elsewhere (Törrönen et al, 2020a). Also, this concern shows how female drinking behaviour faces more intensive social control and moral censure than that of young men.…”
Section: Discussionsupporting
confidence: 48%
“…This article is based on the third interview occasion, including 39 participants with an age range from 17 to 21 years old. Previous results have concentrated on the first and second interview occasions to understand this change when the participants were 15-19 years old (Törrönen et al 2019(Törrönen et al , 2020a(Törrönen et al , 2020b(Törrönen et al , 2020c. The results corroborate previous findings (e.g.…”
Section: Introductionsupporting
confidence: 89%
“…This substantial decrease in young people's drinking has puzzled researchers, politicians, and the public, and little is still known about the mechanisms behind it (Raninen and Livingston 2018). Recent studies have presented multiple explanations, and our study is part of a longitudinal project investigating this change in drinking culture (see Törrönen et al 2019Törrönen et al , 2020aTörrönen et al , 2020bTörrönen et al , 2020c. In this project, young people in Sweden have been interviewed on three occasions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier research showed how social media encouraged displays of drinking [100] and exposed adolescents to alcohol advertising [101]. More recent research suggests that social media also brings with it a range of complexities around self‐presentation, future employment, censorship and engagement with risk that discourages drinking and displays of drunkenness [86,102]. Greater alcohol use among heavy social media users suggests social media platforms continue to reinforce pro‐alcohol norms and encourage socialising with alcohol [103].…”
Section: Introductionmentioning
confidence: 99%